2011
DOI: 10.2215/cjn.08490910
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine and Clinical Outcomes in Chronic Kidney Disease

Abstract: SummaryBackground and objectives Elevated plasma level of asymmetric dimethylarginine (ADMA) have been reported to be associated with endothelial dysfunction and atherosclerosis risk factors, and may predict cardiovascular events in patients with ESRD. In this study, we aimed to assess the association between plasma ADMA and long-term outcome in a cohort of patients with stage 3 to 4 chronic kidney disease (CKD).Design, setting, participants, & measurements From July 2006 to June 2009, 298 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 38 publications
4
46
0
4
Order By: Relevance
“…Interestingly, while ADMA is a known endogenous competitive NOS inhibitor, an established cardiovascular risk marker (31), and is mainly metabolized by dimethylarginine dimethylaminohydrolases (DDAH) (4), the biological role of SDMA is still not completely understood; however, it is believed that it does not directly affect NOS activity (56). Despite this, meta-analysis of multiple studies in patients with renal diseases showed a strong correlation between SDMA and renal function (24,33), suggesting that SDMA may indeed be a potential marker of renal function (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while ADMA is a known endogenous competitive NOS inhibitor, an established cardiovascular risk marker (31), and is mainly metabolized by dimethylarginine dimethylaminohydrolases (DDAH) (4), the biological role of SDMA is still not completely understood; however, it is believed that it does not directly affect NOS activity (56). Despite this, meta-analysis of multiple studies in patients with renal diseases showed a strong correlation between SDMA and renal function (24,33), suggesting that SDMA may indeed be a potential marker of renal function (24).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an abnormal sensory cilia function reported in PKD patients (1,2) disrupts NO biosynthesis, in which primary cilia act as mechanical switches to initiate a NO biochemical reaction (2,40). Therefore, it is not surprising that, within several population studies, plasma levels of the endogenous competitive NOS inhibitor asymmetric dimethylarginine (ADMA) (31,54) were found increased in selected ADPKD patients with preserved GFR (52,59,60).…”
mentioning
confidence: 99%
“…Moreover, ADMA causes eNOS uncoupling, resulting in production of superoxide rather than NO (Antoniades et al, 2009). The raised ADMA levels are reported in diseases associated with endothelial dysfunction such as atherosclerosis, hypertension, diabetes mellitus, hyperlipidemia, ischemic heart disease, and chronic kidney disease (Valkonen et al, 2001;Lu et al, 2011). Thrombomodulin is a transmembrane glycoprotein located on surface of endothelial cells, and functions as an anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of research has since been conducted into the contribution of ADMA to renal disease and it now seems that this endogenous NOS inhibitor is a key player in NO deficit, with levels being predictive of progression to dialysis and death in patients with CKD. 40,41 Accumulation is thought to be because of impaired breakdown of ADMA by the enzymes DDAH 1 and 2. The conditions of oxidative stress inherent in CKD negatively influence the efficacy of DDAH, reducing the catabolism of ADMA.…”
mentioning
confidence: 99%